A Systematic Review Of Candidate Mirnas, Its Targeted Genes And Pathways In Chronic Myeloid Leukemia–an Integrated Bioinformatical Analysis - Nazefah Abdul Hamid; Marjanu Hikmah Elias; Syarifah Faezah Syed Mohamad (Frontiers, 2024)
Indexed by WOS/Scopus/ERA